2003
DOI: 10.1002/bem.10122
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of porcine brain tissue in the transition from life to death at frequencies from 800 to 1900 MHz

Abstract: Ten experiments on pigs were performed to investigate possible postmortem changes of the dielectric properties of brain gray matter in the frequency range of 800-1900 MHz. After keeping the animals in stable anaesthesia for at least 45 min, they were euthanatised by an intravenous injection of hypertonic potassium chloride (KCl), causing cardiac arrest within 3 min. Measurements of the dielectric properties were performed repeatedly from at least 45 min prior to death to 18 h after euthanasia. The anaesthesia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 18 publications
(21 reference statements)
9
44
2
Order By: Relevance
“…For example in Fig.2, at a 5 kHz center point of the typical TMS frequency band (Wagner et al, 2007; Wagner et al, 2004), the recorded relative permittivity magnitudes for the gray matter (solid black line) was approximately 1.5 orders of magnitude higher than those reported in primarily excised tissues of the Institute of Applied Physics Database ((IFAP), 2007) (dotted black line, ‘tissue set 2’) and over five orders of magnitude higher than values most commonly used in past brain stimulation studies(dashed black line, ‘tissue set 1’)(Wagner et al, 2004). Finally, we also found that permittivity and conductivity decreased in magnitude with time post tissue injury/death, approaching many ex-vivo values reported in the literature ((IFAP), 2007), and following tissue trends seen with post mortem changes in higher frequency bands (Schmid et al, 2003)- see Sup. Fig.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…For example in Fig.2, at a 5 kHz center point of the typical TMS frequency band (Wagner et al, 2007; Wagner et al, 2004), the recorded relative permittivity magnitudes for the gray matter (solid black line) was approximately 1.5 orders of magnitude higher than those reported in primarily excised tissues of the Institute of Applied Physics Database ((IFAP), 2007) (dotted black line, ‘tissue set 2’) and over five orders of magnitude higher than values most commonly used in past brain stimulation studies(dashed black line, ‘tissue set 1’)(Wagner et al, 2004). Finally, we also found that permittivity and conductivity decreased in magnitude with time post tissue injury/death, approaching many ex-vivo values reported in the literature ((IFAP), 2007), and following tissue trends seen with post mortem changes in higher frequency bands (Schmid et al, 2003)- see Sup. Fig.…”
Section: Resultssupporting
confidence: 80%
“…Such sizeable differences in the overall permittivity values for gray and white matter are not surprising as the majority of tissue impedance values used for neurostimulation modeling and analysis were developed from ex-vivo models where cell degeneration and/or death has been demonstrated to alter tissue impedance properties in higher frequency bands (Burdette et al, 1986; Schmid et al, 2003; Surowiec et al, 1986)- and as we demonstrated within the neurostimulation frequency band with infarcted tissue (Sup.Fig.2). Furthermore, as discussed by other authors, (Martinsen, 2000; Pethig and Kell, 1987), low frequency dispersion effects appear to be the first to dissipate on tissue death/degeneration (or are potentially affected more by cell/tissue degeneration than those of the higher frequency dispersions).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In one of the most comprehensive studies, Gabriel et al (1996) reported the dielectric properties of a large number of biological tissues including freshly excised bovine and porcine tissue, human autopsy material, and human skin and tongue over a frequency range of 10 Hz-20 GHz. Dielectric data for various human and animal tissues reported in other studies (Foster et al 1979, Surowiec et al 1987, Peyman et al 2001, Schmid et al 2003, Lazebnik et al 2006, Abdilla et al 2013, Sasaki et al 2014 align with the data presented in (Gabriel et al 1996), which is widely used in electromagnetic modeling and assessment of specific absorption rate. Stuchly et al (1982) studied inter-species differences in dielectric properties of skeletal muscle, brain cortex, spleen, and liver tissue between 0.1 and 10 GHz, and reported a very small difference (within system uncertainty) between the same tissues of different species, which led researchers to believe that the data from animal studies can be generalized and used for human tissue modeling.…”
Section: Introductionsupporting
confidence: 75%
“…Few studies are available quantifying the change of the dielectric parameters of animals in the transition from life to death [Burdette and Friederich, 1986;Schmid et al, 2003a]. Human brain tissue was measured over a period of 10 h post mortem [Schmid et al, 2003b].…”
Section: Dependence Of Tissue Parameters On Aging Effectsmentioning
confidence: 99%